Evaluation of coordinated motor ability in handball players - Camacho-Cardenosa, M.; Camacho-Cardenosa, A.; Brazo-Sayavera, J. (Journal of Human Sport & Exercise, 2019)
Modern handball is quicker and more explosive and is made up of varying physically intense movements, which require high-level coordinated motor skills. Although these abilities are considered highly interrelated in team handball players, test involving balls and handball specific movements were used without clear logic and there are no standard test batteries for adults or young players. So, the aim of this review was to summarise current scientific knowledge about how are being assessed the coordinated motor abilities in handball players. Articles published before 10 April 2019 were retrieved by using searches of PubMed, Web of Science and SPORT Discuss. Inclusion criteria were as follows 1) Type of study. All articles published between January 2002 and July 2019 of the English or Spanish languages literature were considered. 2) Type of participant. Studies that evaluated handball players of any age were included and 3) Type of outcome measures: coordinated motor ability outcomes were measured. Ninety-nine original studies were identified in our systematic search from which data were extracted. Accuracy and precision and speed and reaction time are the coordinated motor abilities more evaluated. Only T-test and Illinois agility test show validity and reliability in male and female handball athletes to assess agility. Due to the fact that the included intervention studies were predominantly low in methodological quality and use non-validity test, further high quality studies are needed to develop standard test batteries for adult or young handball players.